A Critical Assessment of Social Responsibility in a Selected Nigerian Cement Company and its Organizational Relationships - Sulaiman T.H; Abalaka, J.N; Ajiteru,S.A.R (International Forum of Researchers and Lecturers, 2025)
The inability of the organization to act in a socially responsible manner and to see why it should act morally has been pointed out by numerous social critics. The tremendous pressure from different interest groups has been assigned by commercial organizations to recognize and address the social issues in which they have a direct stake. The relationship between corporate social responsibility and organizational performance is identified and examined in this study. Nowadays, the majority of businesses employ social responsibility to enhance their reputation, generate revenue, and stay in business. A thorough explanation of social responsibility was provided, including its definition, mode, school of thought, dimensions of involvement, limitations, ways to improve it, and relevance to individuals, organizations, and society at large. One hypothesis was developed to give the opinions of other writers and authors on the topic direction and emphasis in order to conduct this study successfully and efficiently. Statistical methods were used to gather and examine the data, which offer the Consequently, social responsibility improves the performance of organizations.